2019
DOI: 10.1002/prp2.513
|View full text |Cite
|
Sign up to set email alerts
|

Using the novel HiBiT tag to label cell surface relaxin receptors for BRET proximity analysis

Abstract: Relaxin family peptide 1 (RXFP1) is the receptor for relaxin a peptide hormone with important therapeutic potential. Like many G protein‐coupled receptors (GPCRs), RXFP1 has been reported to form homodimers. Given the complex activation mechanism of RXFP1 by relaxin, we wondered whether homodimerization may be explicitly required for receptor activation, and therefore sought to determine if there is any relaxin‐dependent change in RXFP1 proximity at the cell surface. Bioluminescence resonance energy transfer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…The split luciferase assay comprises of two subunits: large BiT protein (LgBiT, 17.8 kDa) and a high affinity complementary peptide (HiBiT, 1.3 kDa) 18 . This assay is useful for measuring intracellular protein interactions (e.g., GPCR homodimerisation) 19 , protein dynamics 20 and cellular internalisation (investigating the role of PIP2) 21 . We express LgBiT as a fusion protein with actin, which localises the LgBiT in the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…The split luciferase assay comprises of two subunits: large BiT protein (LgBiT, 17.8 kDa) and a high affinity complementary peptide (HiBiT, 1.3 kDa) 18 . This assay is useful for measuring intracellular protein interactions (e.g., GPCR homodimerisation) 19 , protein dynamics 20 and cellular internalisation (investigating the role of PIP2) 21 . We express LgBiT as a fusion protein with actin, which localises the LgBiT in the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…[81,117] Recently, surface-specific labeling by the HiBiT-LgBiT system was used to study the potential of the relaxin family receptor-1 (RXFP 1 ) to undergo ligand-induced homodimerization. [118] The assay was based on the distancedependent bioluminescence resonance energy transfer (BRET) between a luciferase-and mCitrine-tagged RXFP 1 . Pairs comprised of the constitutively active Nluc and mCitrine reporters showed BRET responses indicative of ligand-independent formation of RXFP 1 dimers.…”
Section: Complementation Of Reporter Units On Cell Membrane Receptors Guided By Short Peptide Tagsmentioning
confidence: 99%
“…Applied to the monitoring of internalization of the adenosine A1 receptor (A 1 AR) and β 2 adrenergic receptor (β 2 AR) in live cells, a decrease of the luminescent signal is observed when internalized receptors are excluded from interactions with the cell‐impermeable LgBiT [81,117] . Recently, surface‐specific labeling by the HiBiT‐LgBiT system was used to study the potential of the relaxin family receptor‐1 (RXFP 1 ) to undergo ligand‐induced homodimerization [118] . The assay was based on the distance‐dependent bioluminescence resonance energy transfer (BRET) between a luciferase‐ and mCitrine‐tagged RXFP 1 .…”
Section: Visualization Of Receptor Proteins On the Surfaces Of Live Cellsmentioning
confidence: 99%
“…The numerous studies have demonstrated nanoBRET to utilize a broad range of fluorophores—from different fluorescent proteins (CyOFP, red-shifted CyOFP1, mNeonGreen, mScarlet, mCitrine, TurboFP635, mOrange, TagRFP, etc.) [ 185 , 186 , 187 , 188 , 189 , 190 ] to fluorescent dyes (TAMRA, BODIPY, 4-nitro-7-aminobenzofurazan (NBD), Alexa Fluor TM , etc.) [ 191 , 192 , 193 , 194 , 195 ].…”
Section: Ctz-dependent Luciferase Analytical Applicationmentioning
confidence: 99%
“…Comprehensive reviews on NanoBRET methodology and applications have been published recently [ 197 , 198 ]. NanoBRET is successfully used for studying protein–protein interactions [ 184 , 199 ], or investigations on receptor activation [ 190 , 199 , 200 ], oligomerization [ 201 ], conformational states [ 186 ], proximities [ 189 , 202 ], and receptor–ligand interactions [ 200 , 201 , 203 ]. NanoBRET technology has been also applied for in vivo imaging.…”
Section: Ctz-dependent Luciferase Analytical Applicationmentioning
confidence: 99%